Tetragonal distortion in magnetron sputtered bcc-W films with supersaturated carbon. (February 2022) - Mukhamedov, B.O.; Fritze, S.; Ottosson, M.; Osinger, B.; Lewin, E.; Alling, B.; Jansson, U.; Abrikosov, I.A.
Graphical abstract: Highlights: X-ray diffraction experiments show that W films supersaturated with C (2 and 4 at.%) exhibit a tetragonal distortion. Level of tetragonal distortion in W-C films increases with C content. Maximum distortion ( c/a  = 1.02) at 4 at.% C with a  = 3.15–3.16 Å, c  = 3.21–3.22 Å. DFT calculations show that the body centered tetragonal structure has a lower mixing energy than the bcc structure. Calculated E-modulus decreases with increased C content from 405 GPa to 385 GPa and experiments follow the same trend. Abstract: Carbon has a low solid solubility in bcc tungsten at equilibrium. However, metastable supersaturated solid solutions can be synthesized with magnetron sputtering. Here, we present a systematic study on the phase stability and mechanical properties of such supersaturated W–C solid solutions. Θ–2θ scans show a split of the 200/020 and the 002 peaks for supersaturated films which is explained by a tetragonal distortion of the bcc structure. This split increases with increasing C content and is maximized at 4 at.% C, where we observe an a / b axis of 3.15–3.16 Å and a c -axis of 3.21–3.22 Å. We performed first-principles calculations of lattice parameters, mixing enthalpies, elastic constants and polycrystalline elastic moduli for cubic and tetragonal W–C solid solutions. Calculations show that tetragonal structure is more stable than the bcc supersaturated solid solution and the calculated lattice parameters and Young's moduli follow the same trends as the experimental ones as a function of C concentration. The results suggest that supersaturated films with lattice distortion can be used as a design approach to improve the properties of transition metal films with a bcc structure.